STRATEGI PENANGANAN MASALAH SAMPAH DI KOTA TANGERANG MENUJU ZERO WASTE - Sugara, Asep; Pratala, Esaka; Supriyadi, Yudi Nur (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Effective waste management in large cities requires integrated solutions based on improving infrastructure capacity, public awareness, and policies that support more sustainable waste management. To this day, waste remains a major issue for urban communities, such as in Tangerang City. This study aims to find solutions for managing waste so that it no longer becomes a problem but instead transforms into a commodity with economic value. The research method used is qualitative, with data collection conducted through a literature study. The findings conclude that both the government and society must change their perspective on waste, viewing it not as a problem but as a commodity with economic potential. This paper suggests that the Tangerang City Government establish a regional company with a core business in waste production—whether through biocycle farming for organic waste or by setting up an industrial processing system for inorganic waste based on its type